Vi agra falls eaudiobook Bed-and-breakfast mysteries series, book 24. - Daheim, Mary (Bed-And-Breakfast, 2008)
USA Today best-selling author Mary Daheim's juicy mysteries are quickly climbing every fan's list of favorites. This madcap romp features Judith McMonigle Flynn, amateur sleuth and proprietress of Hillside Manor-an historic suburban inn that plays host to more than its fair share of murder and mayhem. Kirkus Reviews calls the series "absolutely intoxicating."